Improving Skills in Writing Explanatory Texts Using the RADEC Model in Grade V Elementary School - Three Rahmadona; R. Teti Rostikawati; Muftah Sharah; Siti Utami (CV. Media Inti Teknologi, 2025)
Background: Writing is a fundamental skill in elementary education, essential for developing students’ cognitive abilities and communication. However, many Indonesian fifth-grade students struggle with explanatory text writing due to limited vocabulary, low motivation, and ineffective teaching models.Aims: This study aims to improve the explanatory text writing skills of grade V students at SDN Lawanggintung 2 through the RADEC (Read, Answer, Discuss, Explain, Create) learning model.Methods: The research employed Classroom Action Research in two cycles with 29 fifth-grade students. Each cycle included planning, action, observation, and reflection. Data were collected through writing tests, classroom observations, and documentation, and analyzed using quantitative and qualitative descriptive methods. The success criterion was set at 75% of students meeting the criteria for achieving learning objectives in Cycle I and 85% in Cycle II.Result: In Cycle I, only 58.6% of students met the criteria for achieving learning objectives, with issues in text structure, vocabulary, and mechanics. After refining the RADEC implementation in Cycle II, 93.1% of students achieved the criteria for achieving learning objectives. Students demonstrated improved organization, richer vocabulary, and better grammatical accuracy.Conclusion: The RADEC model effectively improved students’ explanatory text writing skills by fostering active participation, structured discussion, and collaborative learning. This approach is recommended for Indonesian elementary language classes to address writing skill deficiencies and support 21st-century learning competencies.